2019
DOI: 10.1182/bloodadvances.2019000635
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 S338X clonality is an important determinant of ibrutinib outcomes in patients with Waldenström macroglobulinemia

Abstract: Key Points CXCR4 S338X clonality ≥25% is associated with lower very good partial response and shorter progression-free survival to ibrutinib. CXCR4 S338X clonality assessment represents a novel biomarker to predict outcomes to ibrutinib in Waldenström macroglobulinemia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…Du et al showed that CXCR4 is a valuable prognostic marker in AML, in addition to age, leukocytosis, Fetal Liver Tyrosine Kinase 3 (FLT3) mutant, and extramedullary infiltration. High CXCR4 expression is also an independent risk factor for total survival time in patients with AML [114]. Finally, in multiple myeloma (MM) cells, CXCR4 expression correlated with disease progression [115], chemotherapy resistant MRD [116], and poor prognosis [117], while an increase in the CXCL12 serum expression level was associated with increased osteolytic disease and increased BM angiogenesis [118].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
See 1 more Smart Citation
“…Du et al showed that CXCR4 is a valuable prognostic marker in AML, in addition to age, leukocytosis, Fetal Liver Tyrosine Kinase 3 (FLT3) mutant, and extramedullary infiltration. High CXCR4 expression is also an independent risk factor for total survival time in patients with AML [114]. Finally, in multiple myeloma (MM) cells, CXCR4 expression correlated with disease progression [115], chemotherapy resistant MRD [116], and poor prognosis [117], while an increase in the CXCL12 serum expression level was associated with increased osteolytic disease and increased BM angiogenesis [118].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
“…The mutated CXCR4 receptor continues to generate pro-survival signals upon CXCL12 stimulation. The CXCR4 S338X clonality of ≥ 25% represents a potential biomarker for inferior responses to ibrutinib therapy [114]. Responses to ibrutinib and survival are not only impacted by MYD88 L265P but also by CXCR4 mutations [100].…”
Section: Waldenstrom's Macroglobulinemiamentioning
confidence: 99%
“…In contrast, WM patients with wild-type MYD88 wt usually harbor activating mutations of the NFkappaB pathway downstream of BTK, which is associated with ibrutinib resistance. Approximately one third of WM patients with MYD88 L265P develop subclonal mutations of the chemokine receptor CXCR4 S338X that promote PI3K-AKT and ERK cascades, which are responsible for the acquired ibrutinib resistance (Figure 7) [133,134].…”
Section: Resistance To Ibrutinib and Other Bruton Tyrosine-kinase Inhmentioning
confidence: 99%
“…With 13 patients the majority expressed CXCR4 S338X C > G only and when analyzed in relation to MYD88 L265P showed a clonal distribution of 44.5%. For 7 WM patients who expressed both CXCR4 S338X mutations (C > G and C > A), the fraction of cells expressing CXCR4 S338X relative to MYD88 L265P was around 4% [ 72 , 73 ]. In contrast to data on CXCR4 mutations data on the expression levels of CXCR4 are scarce in WM compared to normal counterparts.…”
Section: Waldenström’s Macroglobulinemia—a Scylla Like Heterogenous Lmentioning
confidence: 99%
“…As seen in relapsed patients responses were depending on the mutational status with a drop in major (94% v 71%) and very good partial (31 v 7%) responses for patients with mutated CXCR4 and delayed time to major responses in this patient group (1.8 v 7.3 months; P = 0.01) [ 64 ]. Responses to Ibrutinib and also PFS depends also on the allelic burden of CXCR4 as was shown in a smaller retrospective analysis of 37 patients treated with ibrutinib: in patients with CXCR4 S338X mutations, clonality of ≥25% was associated with lower response rates and inferior PFS compared to patients with <25% clonality [ 72 ]. Based on the observation, that ibrutinib single agent has less activities in CXCR4 mutated patients and in patients with non-mutated MYD88 and CXCR4, a large international prospective study performed on behalf of the European Consortium for Waldenström’s Macroglobulinemia (ECWM) was initiated, randomizing 150 patients with treatment naive or pretreated WM between ibrutinib plus rituximab or placebo plus rituximab.…”
Section: Waldenström’s Macroglobulinemia—a Scylla Like Heterogenous Lmentioning
confidence: 99%